Assessing responses of reef island seabirds to environmental and anthropogenic drivers - Tristan Berr; Alexandre Millon; Pascal Dumas; Poetea Guehenneuc; Fany Perez; Hélène De Méringo; Julien Baudat‐Franceschi; Éric Vidal (Conservation Biology, 2026)
Tropical insular ecosystems face escalating, cumulative impacts of land‐ and sea‐based ecological threats that jeopardize the long‐term sustainability of their native communities. This joint vulnerability is epitomized by reef island seabirds, which are exposed to reef decline and coastal erosion driven by climate change, reduction in prey availability, human disturbance, and predation by invasive non‐native species. Using site monitoring data acquired from 2000 to 2023, we investigated drivers of species presence and abundance for 15 seabird species (nine Laridae, three Sulidae, two Fregatidae, and one Procellariidae) on 100 coral reef islands around New Caledonia, South Pacific. We established presence and abundance estimates using a compendium of 2805 observations and tested the relative influence of onsite breeding habitat area, characteristics of neighboring marine environments, human visitation, and rodent presence. Responses to ecological drivers varied across species and highlighted distinct functional and taxonomic groups. The presence and abundance of pelagic‐feeding species with high site fidelity were predominantly determined by the availability of breeding habitat, whereas the presence of coastal foragers, including most gulls and terns, appeared constrained by resource availability near breeding sites. Human disturbance had a significant negative influence on the presence of brown noddy ( Anous stolidus ; [−3.41; −1.20]), masked ( Sula dactylatra ; [−3.85; −1.21]), and brown ( Sula leucogaster ; [−4.57; −1.46]) and red‐footed booby ( Sula sula ; [−9.58; −1.20]) and a significant positive influence on the abundance of the commensal silver gull ( Larus novaehollandiae ; [0.03; 0.09]). Our results emphasize the importance of habitat restoration and mitigation of human disturbance for preserving breeding sites of pelagic‐feeding species. However, it may be difficult to sustain populations of coastal seabirds whose presence is mostly driven by small‐scale prey distribution. Thus, a comprehensive approach that fully considers the functional diversity of target seabird communities is needed.

Landscape Structure Shapes the Equilibrium Between Migratory and Sedentary Species in Avian Breeding Communities Along an Altitudinal Gradient - Charlotte Rault; Yoann Le Bagousse‐Pinguet; Amine Flitti; Catherine Godefroid; Agathe Leriche; Alexandre Millon (Journal of Biogeography, 2026)
Aim Human land use shapes landscapes and threatens avian biodiversity, yet its interaction with altitudinal gradients and the consequences for the assembly of long‐distance migratory and sedentary bird communities remain poorly understood. Location Southern France. Taxon Avian breeding communities. Method We examined the changes in the migratory–sedentary ratio (the relative proportion of migratory versus sedentary species) in avian breeding communities (5 × 5 km resolution) in response to a regional‐scale altitudinal gradient (4000 m), in interaction with landscape structure (landscape heterogeneity and forest cover) and species richness. Results We detected interactions between altitude, landscape structure and species richness influencing the migratory: sedentary ratio. This highlights the complex responses of avian communities to both abiotic and biotic drivers. Reduced habitat diversity and evenness at lower altitudes promoted the occurrence of migratory species. While increasing forest cover generally promotes bird species richness, our results showed that its effect on the migratory: sedentary ratio differ between altitudinal belts. Specifically, forest cover was associated with a decrease in the proportion of migratory species at lower altitudes but with an increase at higher altitudes. Finally, increasing total bird richness altered the equilibrium at lower altitudes, where the richest communities (above ~117 bird species) hosted more migratory species than expected from the regional pool. We hypothesise that adding migratory rather than sedentary species to the richest communities reduces competitive interactions for resources and limits niche saturation. Main Conclusions Understanding interactions among environmental drivers is essential for predicting the assemblage of avian communities. Our results identify specific environmental conditions that promote or threaten the richness of migratory and sedentary bird species and thus provide insights to inform conservation actions and policy decisions aimed at mitigating the impacts of environmental change on avian communities.

Echoes of the Past: Long‐Term Climate Stability Shapes Functional and Phylogenetic Diversity in Euro‐Mediterranean Forests - Camille Magneville; Manuel Cartereau; Juan Antonio Hernández‐Agüero; Elysa Silva; Emma‐Liina Marjakangas; Eva Moracho Martinez; Geordie Biffoni; Gabriele Casazza; Vassiliki I. Kati; Ioannis P. Kokkoris; Yoann Le Bagousse‐Pinguet; Frédéric Médail; et al. (Global Ecology and Biogeography, 2025)
Aim Understanding the relative influence of past and present environmental and anthropogenic drivers on biodiversity is crucial for predicting future biodiversity trends. We assessed how past climate stability, present climate, habitat characteristics, disturbances (fire and herbivory), and past and present land use shape current functional and phylogenetic diversity across multiple taxa. Location Euro‐Mediterranean forests. Time Period From Last Glacial Maximum to Present Day. Major Taxa Studied Trees, birds, butterflies, reptiles, and mammals. Methods We quantified standardised functional and phylogenetic diversity across three dimensions: richness, dispersion, and originality for five taxonomic groups. Focusing on 54 individual drivers, we applied random forests to evaluate the importance of broad categories of drivers and understand how individual drivers impact each diversity dimension. Results Past temperature stability since the Last Glacial Maximum emerged as a dominant driver of functional and phylogenetic diversity across taxa. Stability was associated with higher functional and phylogenetic richness and dispersion, whereas unstable past climates were linked to lower diversity. Herbivory also played a significant role, though it was less influential than the past climate, particularly for trees and reptiles, whereas the present climate influenced birds' functional diversity. Fire intensity and surface, and land use in the present and past had limited importance, likely because of the study grain resolution. Main Conclusions Our findings underscore that long‐term climate conditions continue to influence biodiversity patterns across various taxa. This highlights the importance of considering both past legacies and present conditions when assessing biodiversity responses to future climate change. Lastly, we revealed dimension and taxon‐specific responses to drivers, reinforcing the need for integrative biodiversity frameworks that incorporate multiple facets and dimensions of biodiversity across different taxa to get a more nuanced understanding of how biodiversity is structured and maintained.

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

Seabird and reef conservation must include coral islands - Tristan Berr; Maria P. Dias; Serge Andréfouët; Tammy Davies; Jonathan Handley; Matthieu Le Corre; Alexandre Millon; Éric Vidal (Trends in Ecology & Evolution, 2023)

Make flying-fox hunting sustainable again: Comparing expected demographic effectiveness and hunters’ acceptance of more restrictive regulations - Malik Oedin; Fabrice Brescia; Eric Vidal; Alexandre Millon (Ambio, 2022)

Proximate causes and fitness consequences of double brooding in female barn owls - Jabi Zabala; Xavier Lambin; Julien Soufflot; Philibert Soufflot; Delphine Chenesseau; Alexandre Millon (Oecologia, 2020)

Assessing the effectiveness of bird rehabilitation: temporarily captive-reared Little Owls (Athene noctua) experience a similar recruitment rate as wild birds - Olivier Hameau; Alexandre Millon (Journal of Ornithology, 2019)

Dampening prey cycle overrides the impact of climate change on predator population dynamics: a long‐term demographic study on tawny owls - Alexandre Millon; Steve J. Petty; Brian Little; Olivier Gimenez; Thomas Cornulier; Xavier Lambin (Global Change Biology, 2014)